Sistem Merit di Bawah Tekanan Regulasi: Seleksi dan Penempatan PPPK di Badan Pengawas Pemilihan Umum - Syah Rizal Humardani; Abdul Rahman Mansyur; Muhammad Sany Utsman (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study analyzes merit system implementation in Bawaslu’s 2024 PPPK recruitment. Prior research on public sector HRM has examined merit compliance primarily at the regulatory and institutional level, leaving underexplored the organizational mechanisms through which large-scale structural mandates, particularly the imperative to absorb non-civil servant workers, interact with and distort selection and placement practices. This study addresses that gap through a qualitative interpretive case study. Data were collected via in-depth interviews with key informants directly involved in HR planning and procurement, supplemented by document analysis and literature review. Findings show that the fixed placement policy, which predetermined each position based on the candidate’s prior non-civil servant role, reduced selection from an evaluative mechanism to an administrative formality, decoupling selection outcomes from placement decisions. Placement accuracy reached only 46.7%, reflecting widespread person–job mismatch. Limited utilization of job analysis (Anjab) and workload analysis (ABK) further degraded placement quality, with organizational consequences including reduced early-stage productivity, heightened supervisory demands, and prolonged adaptation periods. This study contributes to the literature by conceptualizing formal compliance–substantive meritocracy gap as a structural by-product of large-scale non-ASN regularization policy, and by proposing a merit-integrated placement model as a corrective framework.